Dampak Corporate Social Responsibility (CSR) terhadap Kesejahteraan Masyarakat di Provinsi Jawa Tengah - Rully Noor Oktaviana (LITERATUS, 2022)
Poverty is the main problem in developing countries such as Indonesia, Java Island is the island with the largest population in Indonesia, one of which has a percentage of poverty rate above the national poverty percentage, namely Central Java Province with a percentage of 11.79% in 2021. Central Java Province has 29 regencies and 6 cities. It is seen that the city of Semarang has the lowest percentage of poverty in the province of Central Java, so the city of Semarang was taken as one of the samples in this study, using survey methods and descriptive analysis. The goal is to find out the strategies carried out by the city of Semarang in reducing poverty or improving the welfare of its people. The government through a CSR program with data collection and transparency every period through the Semarang City Government website provides transparency and budget realization that can be adjusted to the needs of the community, so that the welfare of the community increases and the burden of the REGIONAL BUDGET is not too large. Corporate Social Responsibility (CSR) is the company's responsibility to the community and the surrounding environment legally, between the company and the community synergizes to develop its life, the company gets a good image and trust from the community so that the company in the long run can show its existence and the community can improve its welfare. CSR programs not only provide funding but also provide skills, entrepreneurial training or recruitment of employees from the surrounding community. From the sample, an online CSR report (Silap CSR) is currently being made by the Central Java Provincial Government to conduct routine company data collection on CSR so that its programs can be adjusted to the needs of the community/ community, so that a decrease in the percentage of poverty will occur as in the city of Semarang. Currently, there are 217 companies in Central Java Province that will contribute to CSR activities.